(3GOGQI GdeRGQY (B/s - (3GdeUQj, CMeO eMeOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 1996)
(3GdbhGYO GdYGeI ddGOGQI (B-(3WHjZI fTGW GdeRGQY (B-(3Cge GdeTGcd (B-(3YQV dHYV GdMGdGJ GdYedjI ddeRGQY (B-(3eRGQY GdTHGH(B-(3eTQhY eQHhW ddeRGQY GdSecjI (B-(3eTGQjY eDSSI aQjOjT fGQeGf(B-(3eRGQY GdJHMRGjOBd fgGfs
(3jHdjhZQGajG U(B.96s
Keywords: (3GdRQGYI , GbJUGO GdeRGQY , GdeRGQYs